2005
DOI: 10.1039/b503282m
|View full text |Cite
|
Sign up to set email alerts
|

Towards multifunctional antioxidants: synthesis, electrochemistry, in vitro and cell culture evaluation of compounds with ligand/catalytic properties

Abstract: Numerous human diseases are linked to a biochemical condition known as oxidative stress (OS). Antioxidants are therefore becoming increasingly important as potential disease prevention and therapeutic agents. Since OS is a multi-stressor event, agents combining a range of different antioxidant properties, such as redox catalysis and metal binding, might be more effective and selective than mono-functional agents. Selenium derivatives of aniline and pyridine combine redox activity with metal binding properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…More recently, coordination of sulfur and selenium compounds with metal ions has been proposed as an additional antioxidant mechanism [12,13,15,16]. Collins et al have reported selenium-copper complexes that utilize both metal binding and ROS scavenging in oxidative stress prevention [28]. Our research has demonstrated that metal coordination is required for inhibition of copper-and ironmediated DNA damage by sulfur, oxo-sulfur, and selenium compounds [12,13,15,16].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…More recently, coordination of sulfur and selenium compounds with metal ions has been proposed as an additional antioxidant mechanism [12,13,15,16]. Collins et al have reported selenium-copper complexes that utilize both metal binding and ROS scavenging in oxidative stress prevention [28]. Our research has demonstrated that metal coordination is required for inhibition of copper-and ironmediated DNA damage by sulfur, oxo-sulfur, and selenium compounds [12,13,15,16].…”
Section: Introductionmentioning
confidence: 56%
“…However, 2-aniline disulfide showed significantly larger shifts in the copper reduction potential than the corresponding diselenide (-225 mV compared to -50 mV, respectively), and these sulfur-containing compounds did not exhibit GPx activity. Taken together, these results suggest a protective role for selenium compounds through multiple antioxidant mechanisms [28].…”
Section: Metal-binding Mechanisms For Selenium Antioxidant Activitymentioning
confidence: 74%
“…The pyridyl metal chalcogenolates act as better single source precursors of semiconducting materials compared to its alkyl/aryl congeners [4,5]. In biochemistry, selenium derivatives of quinoline and pyridine, because of their superior redox catalytic and metal binding capabilities, act as effective and selective antioxidants when compared with the mono-functional arylselenium compounds [6]. The pyridyl and picolyl chalcogens [7e13] have been known for some time and have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is characterized by an excessive increase in the intracellular oxidizing species, such as reactive oxygen species (ROS), which is involved in the loss of antioxidant defense capacity (Collins et al, 2005). It is closely connected with various medical conditions including aging, atherosclerosis, cancer, neurodegenerative disorders, and DM.…”
Section: Introductionmentioning
confidence: 99%